Government Regulation Sub-Factors and Housing Supply: A Conceptual Framework - Mohamad Asroun, Noryanto Asroun; Aliasak, Mohd Hasrol Haffiz; Abu Bakar, Mohd Afandi (Journal of Technology Management and Business, 2021)
Government regulation is one of the additional factors when examining the influence of land regulations by local authorities on the housing supply. Specifically, this factor is taken into consideration to investigate the effect of city-specific factors on housing supply elasticities. Some government regulation sub-factors usually proxied by index value obtained from the Wharton Residential Land Use Regulation Index (WRLURI). However, the index value is limited to a specific year and not distributed on short term or long-term basis due to data unavailability. This paper reviews the effect of government regulation sub-factors examined by the previous studies to develop a conceptual framework using time series data when the data is available. The findings of this analysis revealed that new studies should explore times series data for sub-factors such as number of restrictions, number of governing bodies, duration for subdivision approval, and the number of growth management policies.